THE PREVALENCE OF SELF-MEDICATION PRACTICE AMONG NON-MEDICAL STUDENTS OF ALEPPO UNIVERSITY - Al-kayali, Rawaa; BAYAN MSLATY; RIMA BARAKAT; HAYA NAKAMI; MUHAMMED KASSARA; NOUR A ALRAHAMAN (Innovare Journal Health Sciences, 2017)
Objective: This study aims to evaluate the prevalence of self-medication among the non-medical students of Aleppo University and assessed the factors related to this practice. Methods: Descriptive cross sectional questionnaire based study was conducted among undergraduates students in different non-medical faculties within Aleppo university using prevalidated structured questionnaires. Â Results: The prevalence of self-medication in this study was 59% with most frequently reported symptom being headache (95.2%) followed by fever (76.5%). The two main reasons for self-medication were the frequency of disease (79.8%) and knowing its treatment (39.5%). Antitussive (72%) and vitamine (65.3%) were the two most frequently consumed medications (92.1%) as pharmacy the main source of drugs to practice self-medication. Â Conclusion: the potential problems of self-medication should be emphasized to the students and education on irrational use of drug should be advocated.